A comparison of shear bond strength of brackets bonded to zirconia - Knott Hannah; Xu Xiaoming; Kee Edwin; Yu Qingzhao; Armbruster Paul; Ballard Richard (Sciendo, 2021)
Purpose: The objective of this study was to compare the shear bond strength (SBS) of ceramic orthodontic brackets bonded to highly translucent zirconia surfaces following the use of two different primers.